CO2 as an Oxidant for High-Temperature Reactions - Kawi, Sibudjing; Kathiraser, Yasotha (Frontiers in Energy Research, 2015)
This paper presents a review on the developments in catalyst technology for the reactions utilizing CO2 for high temperature applications. These include dehydrogenation of alkanes to olefins, the dehydrogenation of ethylbenzene to styrene and finally CO2 reforming of hydrocarbon feedstock (i.e. methane) and alcohols. Aspects on the various reaction pathways are also highlighted. The literature on the role of promoters and catalyst development is critically evaluated. Most of the reactions discussed in this review are exploited in industries and related to on-going processes, thus providing extensive data from literature. However some reactions, such as CO2 reforming of ethanol and glycerol which have not reached industrial scale are also reviewed owing to their great potential in terms of sustainability which are essential as energy for the future. This review further illustrates the building-up of knowledge which shows the role of support and catalysts for each reaction and the underlying linkage between certain catalysts which can be adapted for the multiple CO2-related reactions.